Development of investment activities in the automobile industry of Uzbekistan in the conditions of the digital economy - Omilovna, Kasimova Nozima (Global Academy of Business Studies, 2024)
Purpose: This study examines innovative indicators of industrial growth reserves. Activating innovative factors is the most difficult but promising way to increase industrial production. Research Methodology: This study examines the factors influencing nanoinvestment activities on increasing the efficiency of economic indicators of enterprises in the automotive industry, the classification of investments, methods of assessment in the study of existing problems in the national automotive industry market, and methods of analysis based on the presented approaches. Results: The analysis made it possible identified significant reserves in increasing the level of capacity utilization, increasing labor productivity, modernizing fixed assets, and diversifying and increasing the competitiveness of the industry. Conclusions: This study concludes that industrial modernization, supported by nanoinvestments and innovation policies, provides a sustainable trajectory for growth. Enhancing innovation ecosystems, encouraging strategic investment, and upgrading production capacity are key to addressing the current structural weaknesses. Limitations: The scope of the analysis is limited to the national automotive industry and does not fully incorporate global market fluctuations, long-term investment risks, or external macroeconomic shocks, which may influence the results. Contribution: This study integrates nanoinvestment into the broader discussion of industrial growth reserves, offers a structured classification of investment mechanisms, and provides practical insights for policymakers and industry stakeholders seeking to achieve competitiveness through innovation.